Public sector reform in the Commonwealth Caribbean : a review of recent experiences - Sutton, Paul (The Centre for International Governance Innovation BrightonGB, 2008)
Examines the recent experience of the Commonwealth Caribbean with a particular focus on the successes and failures of New Public Management as a strategy for reform.